Efektivitas Model Pembelajaran Kooperatif Tipe Teams-Games-Tournament (TGT) Terhadap Sikap Sosial Siswa Kelas V SDN 1 Padangbulia Tahun Ajaran 2019/2020 - Made Adi Nugraha Tristaningrat; Komang Trisna Mahartini; Luh Novi Kusuma Dewi (Edukasi: Jurnal Pendidikan Dasar, 2020)
This research aims to provide the effectiveness of the use of innovative learning in the social attitudes of students. Education is one of the components that contribute to the success of nation development. The most notable improvement in  student  activity  during  the  learning  process  by  using  the  Teams-Games-Tournament (TGT) cooperative learning model has increased The  most  notable  improvement  is  that  the  social  skills  of  grade  V students at SD N 1 Padangbulia are shown in the observation results of students ' social skills towards classroom learning. The most prominent aspect of social skills is the aspect of collaborating with others and the aspect of caring. Keywords: cooperative, social, TGT